(untitled) (Argos, 2025)
In this paper we shall try to show that in the Euthydemus Plato develops a critic of the Megarian’s dialectic, which aims to point out the problematical sides of language theory underpinning the eristic procedure. Specifically, Plato shows that the lack of a criterion of truth leads them to commit to statements that undermine the foundations of dialectic.